La motricidad fina en el proceso de la iniciación. de la escritura en niños de 5 años de la Unidad Educativa Andes College - Silva Silva, Erick Andrés (2024)
The present investigation was carried out in the Andes College Educational Unit in the city of Riobamba, Province of Chimborazo; its main objective is to determine the importance of fine motor skills in the process of initiation of writing in five-year-old children in the "Andes College" Educational Unit. The research was based on references from reliable bibliographic documents such as books, articles, and national and international university repositories. For descriptive-level studies, the methodology used is a mixture of non-experimental approaches involving the analysis and collection of qualitative and quantitative data, besides having a non-experimental design due to the lack of manipulation of variables, being documentary research. The population was in the first year of primary education with 15 children. The technique applied was observation, and as an instrument, an observation sheet based on the topic, ten indicators were used in this sheet. It is important to note that fine motor skills play a crucial role in a child's developmental process, particularly during the pre-writing period. This study underscores the significance of incorporating play-based activities to enhance fine motor skills, specifically the development of the child's digital pincer. Such interventions can lead to the optimal development of fine motor skills, which in turn can significantly influence the child's writing readiness.